PENGEMBANGAN VIDEO ANIMASI BERBASIS PENDIDIKAN KARAKTER UNTUK MENINGKATKAN SIKAP TOLERANSI DAN ANTI BULLYING DI SEKOLAH DASAR - Renni Ramadhani Lubis; Titin Rahmyanti Rambe; Wina Mariana Parinduri (Universitas Negeri Medan, 2026)
This study uses a research and development (R&D) method that aims to produce a product in the form of an animated video based on character education to increase tolerance and anti-bullying attitudes in elementary school students. The development model used is addie which includes five stages, namely analysis, design, development, implementation, and evaluation. This study was conducted at SD Negeri 050657 Stabat. The research subjects were 25 fifth grade students consisting of 18 male students and 7 female students. The object of the research was an animated video based on character education. Data collection techniques used were observation, interviews and questionnaires. Data analysis techniques used in this study included qualitative and quantitative data analysis. Based on the results of the study, it is known that the validation results from media experts show a percentage of 93.75% with a very feasible category, while the validation results from material experts obtained a percentage of 89.90% which is also included in the very feasible category, and the results of the analysis of the effectiveness of animated videos based on character education show that 17 students (68%) are in the very good category, 7 students (28%) are in the good category, and 1 student (4%) is in the sufficient category, while no students are in the less category. Thus, it can be concluded that the animated videos based on character education developed in this study are classified as feasible and effective in increasing tolerance and anti-bullying attitudes in grade V students of SD Negeri 050657 Stabat.